The inhibition of warm advection on the southward expansion of sea ice during early winter in the Bering Sea - Wang, Weibo; Su, Jie; Jing, Chunsheng; Guo, Xiaogang (Frontiers in Marine Science, 2022)
Recent observations demonstrate that the Bering Sea exhibits a substantial positive trend of sea ice area increment (ΔSIA, difference in SIA between the current and preceding months) in January contrasted to the considerable negative sea ice area (SIA) trend from 1979 to 2020, and the ΔSIA is unrelated to the local wind field anomaly. To better understand the January ΔSIA variability and its physical characteristics, we explore two distinct empirical orthogonal function (EOF) modes of sea ice concentration increments. EOF1 features a reduction in sea ice concentration (SIC) in the south of St. Lawrence Island. EOF2 is characterized by the rise of SIC surrounding St. Lawrence Island. EOF1 is related to the well-known physical process of December strong poleward heat transport in mixed layer depth. During the southward expansion of sea ice, the multiyear variation of the December SST tendency mostly relies on warm advection in the Bering Sea shelf rather than net air-sea heat flux, and the abnormal northeast wind in December no longer plays the role of a dynamic process dominating the ice area expansion, but generates a stronger poleward heat transport in the Bering Sea shelf to inhibit the southward development of sea ice in the later stage. The two physical processes together result in oceanic poleward heat transport regulating the Bering Sea SIA in competition with atmospheric forcing in early winter. Since PC1 (principal component (PC) time series for EOF1) has a high correlation of -0.76 with the maximum SIA in the Bering Sea, it can be used as the prediction index of the Bering Sea maximum SIA.